2013
DOI: 10.1002/bjs.8978
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the cost of major colorectal surgery

Abstract: Excess body fat was associated with higher costs of major colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Regarding rectal cancer surgery, an Australian study showed no differences in clinical outcomes (complications and/or mortality) of patients with BMIs <30 and >30 kg/m 2 whereas a NSQIP study from the United States of America (USA) showed a higher risk of overall morbidity for patients with BMIs >35 kg/m 2 . A study from the USA that analyzed colon cancer procedures found no significant differences in clinical outcomes (complications and/or mortality) between none‐obese and obese patients whereas other studies from New Zealand and the USA have found only increased risks of wound‐related complications for obese patients (no significant differences in severe complications or mortality were found) .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Regarding rectal cancer surgery, an Australian study showed no differences in clinical outcomes (complications and/or mortality) of patients with BMIs <30 and >30 kg/m 2 whereas a NSQIP study from the United States of America (USA) showed a higher risk of overall morbidity for patients with BMIs >35 kg/m 2 . A study from the USA that analyzed colon cancer procedures found no significant differences in clinical outcomes (complications and/or mortality) between none‐obese and obese patients whereas other studies from New Zealand and the USA have found only increased risks of wound‐related complications for obese patients (no significant differences in severe complications or mortality were found) .…”
Section: Discussionmentioning
confidence: 98%
“…However, (multi‐center) evidence regarding whether obesity has a major impact on hospital costs after colorectal cancer surgery remains scarce. A recent single‐center study from New Zealand showed a significant increase in hospital costs for obese patients (>30 kg/m 2 ); however, likely due to a small sample size (n = 345), no distinctions between obesity classes were noted . Two recent multi‐center studies reported diverse results; a study from the USA reported no differences in hospital costs between non‐obese and obese patients, whereas a Japanese study reported a significant increase in hospital costs for obese patients (>30 kg/m 2 ) .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations